Analysis of Community Involvement in Hypertension Prevention Program in Perbarakan Village Pagar Merbau District - Sinaga, Sri Putriani; Liesmayani, Elvi Era; Manalu, Dinar; Sunengsih, Sunengsih (JURNAL PENGMAS KESTRA (JPK), 2025)
Hypertension has become one of the non-communicable diseases with the most affected case growth rate in the contemporary era, especially in rural areas. Community involvement is very important in the success of hypertension prevention programs. The elderly are susceptible to hypertension because body functions decline with age. Other factors that play a role are unhealthy lifestyles, such as the tendency to consume junk food, smoke, drink alcohol, and rarely exercise. Junk food is usually high in calories, fat, salt (sodium), and low in fiber, which can trigger high blood pressure. Cigarettes are also dangerous because the nicotine content can stimulate the release of adrenaline, which can trigger adrenaline secretion. Analysis of community involvement to see the extent to which the community of Perbarakan Village, Pagar Merbau District, participates in the hypertension prevention program. Activities through counseling, blood pressure checks, and training of posyandu cadres. The method used is participatory and directly involves residents, especially the elderly and health cadres. Activities are carried out through health counseling, blood pressure checks, and training of posyandu cadres. Data were collected through observation, interviews, and questionnaires to determine community understanding and participation. The result is that the community already understands hypertension well enough, but active involvement still needs to be improved with a pre-test score of 16.20, while after counseling it increased to 18.86. Therefore, a stronger communication and empowerment strategy is needed so that the community wants to live a healthy life sustainably.